Let squares be constructed on the sides $BC,CA,AB$ of triangle $ABC$, all to the outside of the triangle, and let $A_1,B_1,C_1$ be their centers. Starting from the triangle $A_1B_1C_1$ one analogously obtains a triangle $A_2B_2C_2$. If $S,S_1,S_2$ denote the areas of triangles $ABC,A_1B_1C_1,A_2B_2C_2,$ respectively, prove that $S = 8S_1-4S_2$

Edits: I made several edits to this post and what is on this post now is the most correct version. If anyone wants to provide a geometrical solution to this question that isn't computational, that would be very helpful.


enter image description here

Note: Throughout this solution I will be using the fact that $\vec{a}+\vec{b}+\vec{c} = \vec{0}$. In other words, $a_1 + b_1+c_1 = 0$ and $b_2+c_2 = 0$.

If we let the sides of the triangle $ABC$ be $\vec{a} = \begin{bmatrix} a_1 \\ 0 \end{bmatrix},\vec{b} = \begin{bmatrix} b_1 \\ b_2 \end{bmatrix},\vec{c} = \begin{bmatrix} c_1 \\ c_2 \end{bmatrix}$ oriented counterclockwise, then $$S = \frac{1}{2} \left| \left|\vec{a} \times \vec{b}\right| \right| = \frac{1}{2} \left | \left|\begin{bmatrix} a_1 \\ 0 \\ 0 \end{bmatrix} \times \begin{bmatrix} b_1 \\ b_2 \\ 0 \end{bmatrix} \right | \right | = \frac{1}{2} \left|a_1b_2 \right|.$$

Now notice that by the picture above that $$\vec{KL} = \dfrac{1}{2}R(90^{\circ})\vec{b}+\frac{1}{2}\vec{c}+\frac{1}{2}R(-90^{\circ})\vec{a} = \dfrac{1}{2} \left(\begin{bmatrix} -b_2 \\ b_1 \end{bmatrix}+\begin{bmatrix} c_1 \\ c_2 \end{bmatrix}+\begin{bmatrix} 0 \\ -a_1 \end{bmatrix} \right) = \dfrac{1}{2} \begin{bmatrix} c_1-b_2 \\ b_1+c_2-a_1 \end{bmatrix} = \dfrac{1}{2}\begin{bmatrix} c_1-b_2 \\ -c_1-b_2-2a_1 \end{bmatrix}$$ and $$\vec{LJ} = \dfrac{1}{2}R(-90^{\circ})\vec{c}+\frac{1}{2}\vec{b}+\frac{1}{2}R(90^{\circ}) \vec{a} = \dfrac{1}{2} \left(\begin{bmatrix} c_2 \\ -c_1 \end{bmatrix}+\begin{bmatrix} b_1 \\ b_2 \end{bmatrix}+\begin{bmatrix} 0 \\ a_1 \end{bmatrix} \right) = \dfrac{1}{2} \begin{bmatrix} b_1+c_2 \\ b_2-c_1+a_1 \end{bmatrix} = \dfrac{1}{2} \begin{bmatrix} -a_1-c_1-b_2 \\ b_2-c_1+a_1 \end{bmatrix}.$$

Note: We will need this result for later that $\vec{JK} = \dfrac{1}{2} \left(R(90^{\circ} \cdot) \vec{c}+\vec{a}+R(-90^{\circ}) \cdot \vec{b}\right) = \dfrac{1}{2}\left(\begin{bmatrix} -c_2 \\ c_1 \end{bmatrix}+\begin{bmatrix} a_1 \\ 0 \end{bmatrix}+\begin{bmatrix} b_2 \\ -b_1 \end{bmatrix} \right) = \dfrac{1}{2} \begin{bmatrix} 2b_2+a_1 \\ c_1-b_1 \end{bmatrix}.$

It follows that $$S_1 = \frac{1}{2} \left| \left|\vec{KL} \times \vec{LJ}\right| \right| = \dfrac{1}{8} \left(\left| \left| \begin{bmatrix} c_1-b_2 \\ -c_1-b_2-2a_1 \end{bmatrix} \times \begin{bmatrix} -a_1-c_1-b_2 \\ b_2-c_1+a_1 \end{bmatrix} \right| \right| \right)= \dfrac{1}{8}\left|-2 a_1^2-4 a_1 b_2-2 b_2^2-2 a_1 c_1-2 c_1^2\right|.$$

Finally, to find $S_2$ we apply the same procedure. First notice that $\triangle{KLJ}$ is oriented clockwise. Then that $\vec{WT} = \dfrac{1}{2}R(-90^{\circ}) \cdot \vec{KL} -\dfrac{1}{2}\vec{JK}+\dfrac{1}{2}R(90^{\circ}) \cdot \vec{LJ} $ and $\vec{TQ} = \dfrac{1}{2}R(-90^{\circ}) \cdot \vec{LJ}-\dfrac{1}{2}\vec{KL}+ \dfrac{1}{2}R(90^{\circ}) \cdot \vec{JK} $. Thus, $$\vec{WT} = \dfrac{1}{2} \left(\dfrac{1}{2} \begin{bmatrix}-c_1-b_2-2a_1 \\ -(c_1-b_2) \end{bmatrix} - \dfrac{1}{2} \begin{bmatrix} 2b_2+a_1 \\ 2c_1+a_1 \end{bmatrix}+\dfrac{1}{2} \begin{bmatrix}-(b_2-c_1+a_1) \\ -a_1-c_1-b_2 \end{bmatrix} \right) = \dfrac{1}{4} \begin{bmatrix} -4a_1-4b_2 \\ -2a_1-4c_1 \end{bmatrix}$$ and $$\vec{TQ} = \dfrac{1}{2}\left(\dfrac{1}{2} \begin{bmatrix}b_2-c_1+a_1 \\-(-a_1-c_1-b_2) \end{bmatrix}- \dfrac{1}{2} \begin{bmatrix} c_1-b_2 \\ -c_1-b_2-2a_1 \end{bmatrix} +\dfrac{1}{2} \begin{bmatrix}-(2c_1+a_1) \\ 2b_2+a_1 \end{bmatrix}\right) = \dfrac{1}{4} \begin{bmatrix} -4c_1+2b_2 \\ 4 a_1+4 b_2+2 c_1 \end{bmatrix}.$$

Finally, $$S_2 = \dfrac{1}{2} \left| \left|\vec{WT} \times \vec{TQ}\right| \right| = \dfrac{1}{32} \left |-16 a_1^2-28 a_1 b_2-16 b_2^2-16 a_1 c_1-16 c_1^2 \right |.$$

To verify the equation, we see that $S = 8S_1-4S_2$ is equivalent to $\dfrac{1}{2}\left|a_1b_2 \right| = 8 \left(\dfrac{1}{8} \left |-2 a_1^2-4 a_1 b_2-2 b_2^2-2 a_1 c_1-2 c_1^2 \right| \right)-4 \left(\dfrac{1}{32} \left |-16 a_1^2-28 a_1 b_2-16 b_2^2-16 a_1 c_1-16 c_1^2 \right | \right) = \left |-2 a_1^2-4 a_1 b_2-2 b_2^2-2 a_1 c_1-2 c_1^2 \right|-\dfrac{1}{8} \left|-16 a_1^2-28 a_1 b_2-16 b_2^2-16 a_1 c_1-16 c_1^2\right|.$


As you can see, the last equality looks right but how do I prove it is true for a triangle?


enter image description here

Let me try. Denote that $AB=c$, $BC=a$, $CA=b$. One then has $$S_1 = S + a^2+b^2+c^2 - \left(\sum \frac{1}{2}a\sqrt{2}b\sqrt{2} \sin(C+90^\circ)\right) = S+ a^2 + b^2 + c^2 -\left(\sum ab\cos C\right)$$

$$=S+a^2+b^2+c^2 - \sum \frac{a^2+b^2-c^2}{2} = S+ \frac{1}{2}(a^2+b^2+c^2).$$

In the same way, one has $$S_2 = S_1 + \frac{1}{2}(A_1B_1^2+B_1C_1^2+C_1A_1^2).$$

Note that $A_1B_1^2 = 2a^2+2b^2-2(2ab)\cos(C+90^\circ) = 2a^2+2b^2+4ab\sin C = 2a^2+2b^2 + 8S$.

Thus, $$S_2 = S_1 + \frac{1}{2}(4(a^2+b^2+c^2) + 24S)$$

So $$S_2 = S_1 + 2(a^2+b^2+c^2) + 12S = S_1 + 4(S_1-S)+12S = 5S_1 + 8S.$$

EDIT: I think the case of one angle is more than $90^\circ$ is the same.

enter image description here

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.